Moderate heritability and low evolvability of sperm morphology in a species with high risk of sperm competition, the collared flycatcher Ficedula albicollis - Edme, Anaïs; Zobač, Petr; Korsten, Peter; Albrecht, Tomáš; Schmoll, Tim; Krist, Miloš (Journal of evolutionary biology, 2019)
Spermatozoa represent the morphologically most diverse type of animal cells and show remarkable variation in size across and also within species. To understand the evolution of this diversity, it is important to reveal to what degree this variation is genetic or environmental in origin and whether this depends on species' life histories. Here we applied quantitative genetic methods to a pedigreed multigenerational data set of the collared flycatcher Ficedula albicollis, a passerine bird with high levels of extra-pair paternity, to partition genetic and environmental sources of phenotypic variation in sperm dimensions for the first time in a natural population. Narrow-sense heritability (h2 ) of total sperm length amounted to 0.44 ± 0.14 SE, whereas the corresponding figure for evolvability (estimated as coefficient of additive genetic variation, CVa ) was 0.02 ± 0.003 SE. We also found an increase in total sperm length within individual males between the arrival and nestling period. This seasonal variation may reflect constraints in the production of fully elongated spermatozoa shortly after arrival at the breeding grounds. There was no evidence of an effect of male age on sperm dimensions. In many previous studies on laboratory populations of several insect, mammal and avian species, heritabilities of sperm morphology were higher, whereas evolvabilities were similar. Explanations for the differences in heritability may include variation in the environment (laboratory vs. wild), intensity of sexual selection via sperm competition (high vs. low) and genetic architecture that involves unusual linkage disequilibrium coupled with overdominance in one of the studied species.
Keywords: Quantitative Trait, Heritable; Passeriformes; kvantitativní znak dědičný; Phenotype; mužské pohlaví; biologická evoluce; zvířata; Biological Evolution; Spermatozoa; fenotyp; spermie; Male; Animals